The Extent of the Inclusion and Consideration of Extreme Climate Events and Health in South African Policies; The Case of eThekwini - Meyer, Charné Amy (University of the Witwatersrand, Johannesburg, 2024)
Climatic changes over southern Africa include the increased frequency and intensification of Extreme Climate Events (ECEs) which exacerbate health risks within vulnerable low- and middle-income countries. Examples of health impacts from ECEs include water-, food-, and vector-borne diseases, morbidity, and mortality. Increased interest in ECEs since the beginning of the 21st century strengthened the recognition of the impact thereof on health. Therefore, it is important to analyse policy documents to determine the extent to which they include and comprehend these themes to prepare for and address negative ramifications. This study aims to explore the scope to which policy documents relevant to eThekwini, mention and deliberate the ECE- health nexus. This exploration of existing policies allows a contribution to the nascent literature around the ECE-health intersection and is indicative of possible areas of corrective strategy. This is conducted through a review of relevant policy documents, interviews with key stakeholders, and the analysis of secondary climate and health interview data. Findings reflect a 50% recognition of the ECE-health intersection in policy documents. Stakeholders acknowledge the importance of policy documents recognizing this interconnection. Notably, stakeholders are not aware of such policy documents that currently exist but identify barriers to these policy documents being updated and upheld. Hence, the Municipality does have adaptation strategies in place however, improvements thereof are necessary. Examples include the need for short- term adaptation planning, improved policy implementation, and community education. The lack of such work would exacerbate health concerns and add significant strains on the health sector
A research report submitted in partial fulfillment of the requirements for the degree of Master of Science to the Faculty of Science, Geography, Archaeology, and Environmental Studies, University of the Witwatersrand, Johannesburg, 2024
Keywords: Policy; Extreme Climate Events; Health; eThekwini; Adaptation; UCTD; SDG-13: Climate action